Tryptophan Catabolism as Immune Mechanism of Primary Resistance to Anti-PD-1 - Botticelli, Andrea; Mezi, Silvia; Pomati, Giulia; Cerbelli, Bruna; Cerbelli, Edoardo; Roberto, Michela; Giusti, Raffaele; Cortellini, Alessio; Lionetto, Luana; Scagnoli, Simone; Zizzari, Ilaria Grazia; Nuti, Marianna; et al. (Frontiers in Immunology, 2020)
Background: Clinical trials showed that only a subset of patients benefits from immunotherapy, suggesting the need to identify new predictive biomarker of resistance. Indoleamine-2,3-dioxygenase (IDO) has been proposed as a mechanism of resistance to anti-PD-1 treatment, and serum kynurenine/tryptophan (kyn/trp) ratio represents a possible marker of IDO activity. Methods: Metastatic non-small cell lung cancer (NSCLC), renal cell carcinoma (RCC), and head and neck squamous cell carcinoma (HNSCC) treated with nivolumab as second-line treatment were included in this prospective study. Baseline serum kyn and trp levels were measured by high-performance liquid chromatography to define the kyn/trp ratio. The χ2-test and t-test were applied to compare frequencies and mean values of kyn/trp ratio between subgroups with distinct clinical/pathological features, respectively. Median baseline kyn/trp ratio was defined and used as cutoff in order to stratify the patients. The association between kyn/trp ratio, clinical/pathological characteristics, response, progression-free survival (PFS), and overall survival (OS) was analyzed. Results: Fifty-five patients were included. Mean baseline serum kyn/trp ratio was significantly lower in female than in male patients (0.048 vs. 0.059, respectively, p = 0.044) and in patients with lung metastasis than in others (0.053 vs. 0.080, respectively, p = 0.017). Mean baseline serum kyn/trp ratio was significantly higher in early progressor patients with both squamous and non-squamous NSCLC (p = 0.003) and with a squamous histology cancer (19 squamous NSCLC and 14 HNSCC, p = 0.029). The median value of kyn/trp ratio was 0.06 in the overall population. With the use of median value as cutoff, patients with kyn/trp ratio > 0.06 had a higher risk to develop an early progression (within 3 months) to nivolumab with a trend toward significance (p = 0.064 at multivariate analysis). Patients presenting a baseline kyn/trp ratio ≤0.06 showed a longer PFS [median 8 vs. 3 months; hazard ratio (HR): 0.49; 95% confidence interval (CI) 0.24–1.02; p = 0.058] and a significantly better OS than did those with a kyn/trp ratio > 0.06 (median 16 vs. 4 months; HR: 0.39; 95% CI 0.19–0.82; p = 0.013). Conclusion: Serum kyn/trp ratio could have both prognostic and predictive values in patients with solid tumor treated with immunotherapy, probably reflecting a primary immune-resistant mechanism regardless of the primary tumor histology. Its relative weight is significantly related to gender, site of metastasis, NSCLC, and squamous histology, although these suggestive data need to be confirmed in larger studies.